Climate engineering a normative perspective - Callies, Daniel Edward, 1986- (Lexington Books, 2019)
Should we research, develop, and deploy climate engineering technology? Drawing upon contemporary moral and political theory, this book offers a normative perspective on such questions, ultimately making the case in favor of research and regulation guided by norms of legitimacy, distributive justice, and procedural justice.